1997
DOI: 10.1002/art.1780400206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the synovial cell infiltrate in early rheumatoid synovial tissue in relation to local disease activity

Abstract: Objective. To define variations in the cellular infiltrate and in the expression of monokines in synovial tissue (ST) from rheumatoid arthritis (RA) patients with different durations of disease and different levels of disease activity. Methods. The immunohistologic features of synovial biopsy specimens from 31 patients with early RA (<1 year) and 35 patients with longstanding RA (>5 years) were compared. The possible associations between these features and local disease activity, as measured by the score for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
350
4
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 476 publications
(379 citation statements)
references
References 53 publications
19
350
4
6
Order By: Relevance
“…The combined analysis of cellular complexity, together with a comprehensive overview of the concomitant gene expression profile, provides opportunities for further research. The expression data suggest involvement of two distinct disease processes in rheumatoid pathogenesis, which is in accordance with data from several studies that indicated biologic heterogeneity in RA (6,19,33,34). The existence of a spectrum of molecular variation that may be translated into distinct pathophysiologic mechanisms at the site of the lesion would fit a model proposed by Firestein and Zvaifler (3), who suggested two processes in the destruction stage of RA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The combined analysis of cellular complexity, together with a comprehensive overview of the concomitant gene expression profile, provides opportunities for further research. The expression data suggest involvement of two distinct disease processes in rheumatoid pathogenesis, which is in accordance with data from several studies that indicated biologic heterogeneity in RA (6,19,33,34). The existence of a spectrum of molecular variation that may be translated into distinct pathophysiologic mechanisms at the site of the lesion would fit a model proposed by Firestein and Zvaifler (3), who suggested two processes in the destruction stage of RA.…”
Section: Discussionsupporting
confidence: 88%
“…The presence of such characteristic cell-specific gene clusters correlates with reported data on infiltration of mononuclear cells into the rheumatoid synovium (6,19,33,34). Overexpression of these gene clusters is consistent with increased ESRs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…T cells are thought to play a role in the induction phase of the disease, supporting the activation of collagen-specific B cells, but have a less No production of rheumatoid factor * RA ϭ rheumatoid arthritis; CIA ϭ collagen-induced arthritis; MHC ϭ major histocompatibility complex; NSAIDs ϭ nonsteroidal antiinflammatory drugs; PGIA ϭ proteoglycan-induced arthritis; AIA ϭ adjuvant-induced arthritis; SCW ϭ streptococcal cell wall; STIA ϭ serum transfer-induced arthritis; Tg ϭ transgenic; TNF ϭ tumor necrosis factor. (9), which is in contrast to RA synovium, where macrophages constitute the major phagocytic cell population (10). Cytokines influence disease induction and development in a time-dependent manner (2) ( Table 3).…”
Section: Animal Models Of Rheumatoid Arthritismentioning
confidence: 99%
“…IL-6 is abundantly expressed in both the synovial fluid and serum of patients with RA (102); its expression in synovial tissue is significantly correlated with clinical signs and symptoms of arthritis (10). It has a variety of functions, including initiation of the acute-phase response, activation of vascular endothelial cells, and induction of B cell and T cell differentiation (89,103).…”
Section: From Animal Models Toward the Clinicmentioning
confidence: 99%